2020
DOI: 10.1186/s13578-020-00484-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification of atypical mitogen-activated protein kinase MAPK4 as a novel regulator in acute lung injury

Abstract: Background Acute lung injury (ALI) is a serious disease with highly morbidity and mortality that causes serious health problems worldwide. Atypical mitogen activated protein kinases (MAPKs) play critical roles in the development of tissues and have been proposed as promising therapeutic targets for various diseases. However, the potential role of atypical MAPKs in ALI remains elusive. In this study, we investigated the role of atypical MAPKs family member MAPK4 in ALI using LPS-induced murine A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Four of these sites were hypomethylated and annotated to the MAPK4 , HNRNPM , and PTGIR genes. MAPK4 is an atypical kinase involved with the AKT/mTOR signaling pathway, and overexpression is associated with acute lung injury and cancers 63 , 64 . Similarly, the HNRNPM and PTGIR proteins have been shown to promote cancerous cell growth and be associated with poorer oncogenic outcomes 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Four of these sites were hypomethylated and annotated to the MAPK4 , HNRNPM , and PTGIR genes. MAPK4 is an atypical kinase involved with the AKT/mTOR signaling pathway, and overexpression is associated with acute lung injury and cancers 63 , 64 . Similarly, the HNRNPM and PTGIR proteins have been shown to promote cancerous cell growth and be associated with poorer oncogenic outcomes 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hypomethylation within the exons of the ephrin type-A receptor ( Epha2 ) is reported to mediate brain endothelial cell TJ disruption in inflammatory conditions [ 75 ]. Other unfavorable factors for BBB recovery are the activation of the Rho GTPase RhoA and CDC42 effector protein 4 ( Cdc42ep4 ), both indicated in regulating actin remodeling, stress fiber formation, and TJ complex disassembly, as well as atypical Map kinase Mapk4 , the overexpression of which shifts cells to a proinflammatory phenotype [ 76 79 ]. Presumably, the balance, or lack thereof, between favorable and unfavorable processes/factors may predict the final outcomes of BBB poststroke recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether there is a certain connection between LPAR5 and LIPH through certain media is worth further exploration. MAPK4 is an atypical MAPK involved in the development of many human diseases 23 , 24 . Wang et al demonstrated that MAPK4 promotes cancer progression by stimulating the AKT/mTOR signaling pathway, which is closely related to cell growth, survival, metastasis, metabolism, etc 25 .…”
Section: Discussionmentioning
confidence: 99%